Decoupling Analysis of Energy-Related Carbon Dioxide Emissions from Economic Growth in Poland - Zbigniew Gołaś (Energies, 2023)
This paper addresses the conditions behind energy-related carbon dioxide (CO2) emissions in Poland following its accession to the European Union. The study analyzed some energy, fossil fuel, economic, and environmental indicators, such as energy use, CO2 emissions, driving factors, decoupling elasticity status, and decoupling effort status. It relied on the Kaya identity and Logarithmic Mean Divisia Index (LMDI) in determining the drivers of CO2 emissions. As shown by the results, between 2004 and 2020, energy consumption in Poland grew at an average annual rate of 0.8%, while fossil fuel carbon emissions declined at 0.7% per year. Energy intensity was found to be the key force behind the reduction in CO2 emissions, whereas rapid economic growth was the main driver of CO2 emissions. While other factors, i.e., carbon intensity, energy mix, and population, also contributed to reducing the emissions, they had a much smaller—if not marginal—effect. In turn, the decoupling elasticity analysis showed that Poland mostly witnessed strong decoupling states, which means a strong decoupling of CO2 emissions from economic growth. Furthermore, it follows from the decoupling effort analysis that strong decoupling effort statuses prevailed throughout the study period, suggesting that the changes in the considered factors significantly contributed to reducing CO2 emissions. However, both the decoupling elasticity indices and the decoupling effort indices revealed the presence of an adverse trend. The above means that Poland witnessed a decline both in the strength of decoupling CO2 emissions from economic growth and in the efficiency of policies and measures designed to reduce CO2 emissions.